2013
DOI: 10.5194/gmd-6-1941-2013
|View full text |Cite
|
Sign up to set email alerts
|

The GREENROOF module (v7.3) for modelling green roof hydrological and energetic performances within TEB

Abstract: Abstract. The need to prepare cities for climate change adaptation requests the urban modeller community to implement sustainable adaptation strategies within their models to be tested against specific city morphologies and scenarios. Greening city roofs is part of these strategies. In this context, the GREENROOF module for TEB (town energy balance) has been developed to model the interactions between buildings and green roof systems at the scale of the city. This module, which combines the ISBA model (Interac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…The focus is to keep the maximum of key processes, while making some approximations in the geometry that are pertinent at block scale (building shapes are averaged into road canyons, only one thermal zone is kept in the buildings, individual windows are averaged into a glazing fraction, etc.). Gardens and greenroofs modules have also been implemented (Lemonsu et al, 2012;DeMunck et al, 2013a). The modeling strategy chosen here for the implementation of solar panels is similar: key processes are kept while some geometrical assumptions are made to avoid unnecessary details of individual buildings.…”
Section: Modeling Strategymentioning
confidence: 99%
“…The focus is to keep the maximum of key processes, while making some approximations in the geometry that are pertinent at block scale (building shapes are averaged into road canyons, only one thermal zone is kept in the buildings, individual windows are averaged into a glazing fraction, etc.). Gardens and greenroofs modules have also been implemented (Lemonsu et al, 2012;DeMunck et al, 2013a). The modeling strategy chosen here for the implementation of solar panels is similar: key processes are kept while some geometrical assumptions are made to avoid unnecessary details of individual buildings.…”
Section: Modeling Strategymentioning
confidence: 99%
“…ground vegetation, street trees, vegetated walls and green roofs). This required development of the TEB model (Masson, 2000) to consider, and further evaluate, such scenarios (Lemonsu et al, 2012;De Munck et al, 2013;De Munck et al, 2018;Redon et al, 2017). Using a complete vegetation and soil model to represent green roofs, De Munck et al (2018) showed that green roofs would not have a significant effect on air temperature at street level, contrary to ground vegetation and trees.…”
Section: Main Challenges Scientific Novelty and Innovation Of Solutimentioning
confidence: 99%
“…The model developments also permitted testing of implementing alternative urban energy systems; Masson et al (2014b) showed that solar panels could be widely implemented without adverse effect on the UHI (where a slight cooling, of approximately 0.2°C, was simulated). Air conditioning can increase night-time temperatures in more densely built parts of Paris by more than 1°C (De Munck et al, 2013), so a Building Energy Module is also a desirable component of the modeling system to evaluate anthropogenic heat fluxes to the atmosphere. Energetic human behavior has been including in TEB (Schoetter et al, 2017) thanks to a collaboration with sociologists ).…”
Section: Main Challenges Scientific Novelty and Innovation Of Solutimentioning
confidence: 99%
“…Reversely, the microclimate within the canyon can be impacted by the modification of surface energy exchanges due to the presence of vegetation at the ground, especially by its evapotranspiration. A module of extensive green roofs was also developed (de Munck et al, 2013) still using the ISBA model to simulate the hydrological and energetic functioning of the green roofs, as well as the energy exchanges with atmosphere and the thermal coupling with the buildings on which they are installed.…”
Section: Previous Developments and General Approachmentioning
confidence: 99%